Clinical symptoms of limited exercise capacity linked to AAI‐DDD functionality: An in silico and in vivo approach. - Heggermont, Ward; Iliodromitis, Konstantinos; Van Bockstal, Koen; Backers, Jos; Lau, Chirik‐Wah; Missiaen, Dieter; De Cooman, Jan; Timmermans, Willy; Geelen, Peter; De Potter, Tom (Pacing & Clinical Electrophysiology, 2021)
Background: Exercise capacity is an important aspect of quality of life in patients undergoing pacemaker implantation. Device algorithms for ventricular pacing avoidance have been developed to avoid unnecessary and potentially harmful effects of right ventricular pacing. However, little data exists on the immediate response of these algorithms to sudden AV block during exercise. Methods: The ventricular pacing avoidance algorithms of four pacemaker manufacturers were tested in an ex‐vivo model. The RSIM‐1500‐USB Device‐Interactive Heart Simulator (Rivertek Medical Systems, Inc.) was used to simulate three different scenarios: the first one starting with an initially conducted atrial pacing rate of 60 min−1, the second one starting with an atrial rate of 120 min−1 and finally a scenario starting with an atrial rate of 150 min−1. In all three scenarios, the initially conducted atrial rate was followed by a sudden, long lasting episode of third‐degree AV‐block. The response to those scenarios was recorded for each of the (brand‐specific) ventricular pacing avoidance algorithms. Results: In the first scenario, the simulation resulted in a ventricular pause of 1333 ms (Boston Scientific), 2000 ms (Medtronic and Microport), and 2340 ms (Biotronik). In the second and third scenario, different results were observed across devices. All simulations of the second and third scenario resulted in repetitive 2:1 block response (during eight cycles) in Boston Scientific and Biotronik devices. These scenarios were confirmed in patient cases. Conclusion: Simulator based observations of unanticipated pacemaker‐induced 2:1 block response during exercise may explain clinical symptoms experienced by some patients having a two‐chamber pacemaker.